NEW METHODS OF TEACHING ENGLISH - Babakulova Ziynat Iskandarovna (American Journals Publishing, 2025)
In recent years, many innovative techniques have emerged in teaching English, each corresponding to a different student need and learning styles. Unlike traditional classes, these new approaches do not give students only theoretical knowledge, but also extend the opportunity for them to practice language, develop speech, listening, reading, and writing. Learning English is now taking shape as an interesting and dialogue-based process, rather than a mandatory one. For this reason, their deep study and application in practice are important not only for teachers, but also for students.
Keywords: English, communication, methods, innovative approach, Information Technology, lesson, knowledge, skills, opportunity.